2018
DOI: 10.1088/1361-6498/aaed49
|View full text |Cite
|
Sign up to set email alerts
|

Formation of radioactive waste in Estonian water treatment plants

Abstract: In northern Estonia, higher levels of Ra-226 and Ra-228 concentrations give rise to problems with water treatment plants (WTPs) using Cambrian-Vendian (Cm-V) aquifer. During water treatment processes, radionuclides accumulate in the filter material to a level where the material could be classified as a radioactive material. In order to understand the scope of the problem, a nation-wide survey was carried out among the Cm-V fed treatment plants. Filter material and water samples were collected from 18 Estonian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A study showed that pollutants in plants were mainly caused by human activities, such as industrial sewage, domestic sewage, and agricultural wastewater, which was summarized by cluster analysis and principal component analysis . Some plants could accumulate huge amounts of nitrates, polycyclic aromatic hydrocarbons, antibiotics or other pharmaceutical chemicals, , trace metals, and radioactivity from wastewater . Although the resulting concentration of contaminants in the soil exceeded the environmental quality standards, their presence in plants might meet the food safety guidelines and would not affect the chlorophyll and carbohydrate contents in the leaves, which explained normal growth of our tested plants.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…A study showed that pollutants in plants were mainly caused by human activities, such as industrial sewage, domestic sewage, and agricultural wastewater, which was summarized by cluster analysis and principal component analysis . Some plants could accumulate huge amounts of nitrates, polycyclic aromatic hydrocarbons, antibiotics or other pharmaceutical chemicals, , trace metals, and radioactivity from wastewater . Although the resulting concentration of contaminants in the soil exceeded the environmental quality standards, their presence in plants might meet the food safety guidelines and would not affect the chlorophyll and carbohydrate contents in the leaves, which explained normal growth of our tested plants.…”
Section: Resultsmentioning
confidence: 82%
“…57 Some plants could accumulate huge amounts of nitrates, 58 polycyclic aromatic hydrocarbons, 59 antibiotics 60 or other pharmaceutical chemicals, 61,62 trace metals, 57 and radioactivity from wastewater. 63 Although the resulting concentration of contaminants in the soil exceeded the environmental quality standards, their presence in plants might meet the food safety guidelines and would not affect the chlorophyll and carbohydrate contents in the leaves, 64 which explained normal growth of our tested plants. Nevertheless, further studies are needed to show whether the level of contaminants in the fruits of plants that were investigated were suitable for human nutrition.…”
Section: Resultsmentioning
confidence: 83%
“…Interestingly, the sludges and precipitates of this study had a higher frequency of radium-enriched (Ra-226 > U-238) residues even though the groundwater is of the uranium-type (U-238 > Ra-226). Radium in groundwater occurs mainly in ionic form [8,32], and radium is known to be efficiently removed from water through coprecipitation and adsorption into manganese oxides [31,32]. Finnish groundwater often contains manganese that needs to removed from the drinking water in addition to iron (table 1), so it is a possibility that the formation of manganese oxides during aeration and filtration is involved in the capture of radium to residues, but it was not possible to determine a detailed water chemistry or mineralogy of the residues as a part of this study.…”
Section: Sludges and Precipitatesmentioning
confidence: 99%
“…Internationally, there are studies from e.g. Germany, Spain and Estonia [15,16,25,30,31], but these are from areas where the geology and groundwater chemistry can be very different from Finland.…”
Section: Introductionmentioning
confidence: 99%
“…Hill et al (2017) monitored the concentrations of iron, manganese, 226 Ra, and 228 Ra at different stages of the treatment process for later comparison in terms of removal efficiency and interaction between these elements. Leier et al (2019) studied 18 treatment plants in Estonia and found high concentrations of 226 Ra and 228 Ra, of which they accumulate in the filter material, at a level where the material can be classified as radioactive material. Of the WTPs studied, 16 exceeded the levels allowed in the adopted legislation.…”
Section: Introductionmentioning
confidence: 99%